Atrial fibrillation in chronic heart failure patients with reduced ejection fraction: The CHECK-HF registry. (1st June 2020) - Veenis, Jesse F.; Brunner-La Rocca, Hans-Peter; Linssen, Gerard C.M.; Smeele, Frank J.J.; Wouters, Noëmi T.A.E.; Westendorp, Paul H.M.; Rademaker, Philip C.; Hemels, Martin E.W.; Rienstra, Michiel; Hoes, Arno W.; Brugts, Jasper J.; ,
Abstract: Background: Atrial fibrillation (AF) is common in chronic heart failure (HF) patients and influences the choice and effects of drug and device therapy. In this large real-world HF registry, we studied whether the presence of AF affects the prescription of guideline-recommended HF therapy. Methods: We analyzed 8253 patients with chronic HF with reduced ejection fraction (HFrEF) from 34 Dutch outpatient clinics included in the period between 2013 and 2016 treated according to the 2012 ESC guidelines. Results: 2109 (25.6%) of these patients were in AF (mean age 76.8 ± 9.2 years, 65.0% were men) and 6.144 (74.4%) had no AF (mean age 70.7 ± 12.2 years, 63.6% were men). Patients with AF more often received beta-blockers (81.7% vs. 79.7%, p = 0.04), MRAs (57.1% vs. 51.7%, p < 0.01), diuretics (89.7% vs. 80.6%, p < 0.01) and digoxin (40.1% vs. 9.3%, p < 0.01) compared to patients without AF, whereas they less often receive renin-angiotensin-system (RAS)-inhibitors (76.1% vs. 83.1%, p < 0.01). The number of patients who received beta-blockers, RAS-inhibitor and MRA at ≥50% of the recommended target dose was comparable between those with and without AF (16.6% vs. 15.2%, p = 0.07). Conclusion: In this large cohort of chronic HFrEF patients, the prevalence of AF was high and we observed significant differences in prescription of both guideline-recommended HF between patients with and without AF. Highlights: HFrEF patients with AF received more often beta-blockers, MRA, diuretics and digoxin. HFrEF patients with AF received less often RAS-inhibitors. More insight in the efficacy and adherence of HF therapy in AF patients is needed.